Early life exposure to clonazepam has both short- and long-term effects on seizures induced with pentylenetetrazol (PTZ) - Kubova, Hana; Tsenov, Grygoriy; Conti, Anita; Negri, Alessandro; Roubalova, Lenka; Mares, Pavel (Frontiers in Pharmacology, 2026)
IntroductionThe abrupt cessation of chronic benzodiazepine administration is associated with the development of withdrawal symptoms like increased susceptibility to seizures or seizure development in both animals and humans. Although withdrawal phenomena have been studied in detail in adult animals, information about their development and nature in the immature brain is lacking. Substantial experimental evidence suggests that exposure to BZDs early in life permanently alters brain circuitry and functions. However, the possible long-term modification of seizure propensity has not yet been studied.MethodsClonazepam (CZP) was injected into rat pups daily at a dose of 1 mg/kg for five consecutive days, starting on postnatal day 7 (P7) and continuing until P11. Seizure susceptibility was assessed using a pentylenetetrazol (PTZ)-induced seizure model. PTZ induces three types of seizures in rodents that differ by developmental profile and manifestations: convulsive myoclonic seizures (mS) and generalized tonic-clonic seizures (GTCS), and absence-like rhythmic spike-and-wave EEG activity (RMA). Seizures were induced with a single threshold dose of 50–60 mg/kg on days 2, 4, 7, 10, or 14, or with three additive doses of 20 mg/kg on days 7 and 14, or 3 months after the end of treatment. Convulsions accompanying mS and GTCS were detected behaviorally, and RMA was detected in EEG recordings.ResultsThe effects of early-life CZP exposure on susceptibility to PTZ-induced seizures were highly dependent on the interval after treatment cessation and the seizure type. Cessation of CZP after a single PTZ threshold dose resulted in an increase in seizure severity compared to controls that was driven by an increased incidence of GTCS lasting 1 week (up to P18). Early-life CZP exposure led to decreased latency to the first RMA and increased RMA frequency after the first PTZ dose of 20 mg/kg in adult (P90) animals, but it did not change RMA parameters in juvenile rats.ConclusionAbruptly ceasing clonazepam administration in infant rats results in the development of withdrawal phenomena, represented by a striking increase in seizure propensity. Interestingly, transient augmentation of GABAergic inhibition during critical periods of synaptogenesis and neural network formation and maturation permanently modifies susceptibility to PTZ-induced epileptiform activity.